2018
DOI: 10.1038/s41598-018-24024-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Extraction Ratio (OER) as a Measurement of Hemodialysis (HD) Induced Tissue Hypoxia: A Pilot Study

Abstract: HD tissue hypoxia associates with organ dysfunctions. OER, the ratio between SaO2 and central-venous-oxygen-saturation, could estimate oxygen requirements during sessions, but no data are available. We evaluated OER behavior in 20 HD patients with permanent central venous catheter (CVC) as vascular access. Pre-HD OER (33.6 ± 1.4%; M ± SE) was higher than normal (range 20–30%). HD sessions increased OER to 39.2 ± 1.5% (M ± SE; p < 0.05) by 30′ and to 47.4 ± 1.5% (M ± SE; p < 0.001) by end of treatment (delta 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 21 publications
7
14
0
Order By: Relevance
“…1). This is in perfect agreement with the available evidence (15) of HD related hypoxic stress which is not sensed by the patients and is not detected by commonly available parameters like BP and HR (5,6,15,25,26,27). Therefore, ∆OER seems to offer a prompt and direct measurement of the hypoxic stress produced by HD and could thus represent a useful tool to identify more fragile patients.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…1). This is in perfect agreement with the available evidence (15) of HD related hypoxic stress which is not sensed by the patients and is not detected by commonly available parameters like BP and HR (5,6,15,25,26,27). Therefore, ∆OER seems to offer a prompt and direct measurement of the hypoxic stress produced by HD and could thus represent a useful tool to identify more fragile patients.…”
Section: Discussionsupporting
confidence: 88%
“…Since OER measurement is handy in dialysis patients with central venous catheter (CVC), we recently evaluated it before and during HD sessions in a pilot study. We demonstrated that patients showing lower resting pre-HD OER values (< 32%) and/or greater OER increments (∆OER >40%) after HD had higher mortality rate (15). Also, in this same work, we could appreciate that OER values are rather stable and repeatable in the single patient, thus pointing to its potential usefulness to describe the hemodynamic capacity of a patient.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…A low input volume indicates atrial insufficiency, a low output volume ventricular insufficiency, and a low ratio might be associated to heart failure in several respects (e.g., decline of the contractile function). The list goes on with the albumin-to-globulin ratio (liver insufficiency, immunodeficiency, auto-immunity, infection, cancer); calciumto-albumin ratio (malnutrition); albumin-to-creatinine ratio (kidney disease); cortisol-to-cortisone ratio (cardiovascular risk); calcitriol-to-calcifediol ratio (renal efficiency); 50 oxigen extration ratio (haemodialysis efficacy); metabolite ratios (type 2 diabetes); 51 and stable isotope ratios (diet). 52 The first component d 1 (major axis) is the direction with maximal variance and its equation can expressed as 34…”
Section: Discussionmentioning
confidence: 99%